1992
DOI: 10.1111/j.1476-5381.1992.tb14367.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential inotropic effects of flosequinan in ventricular muscle from normal ferrets versus patients with end‐stage heart failure

Abstract: tion that is typical of catecholamines. 3 Neither flosequinan (n = 12) nor BTS 53 554, its sulphone metabolite (n = 6) produced a positive inotropic effect or altered the time course of contraction in myocardium from the hearts of patients with end-stage failure. 4 In contrast to milrinone, which produces a positive inotropic effect via phosphodiesterase inhibition, the unresponsiveness of myopathic human myocardium to flosequinan was not restored after intracellular adenosine 3':5'-cyclic monophosphate (cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In one study, flosequinan did not increase contractility with or without forskolin stimulation. 35 In a second report, a positive inotropic action was observed, although only at concentrations somewhat higher than the measured therapeutic range, and forskolin potentiation was present.39 These findings would be consistent with weak phosphodiesterase inhibitor activity.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In one study, flosequinan did not increase contractility with or without forskolin stimulation. 35 In a second report, a positive inotropic action was observed, although only at concentrations somewhat higher than the measured therapeutic range, and forskolin potentiation was present.39 These findings would be consistent with weak phosphodiesterase inhibitor activity.…”
Section: Discussionsupporting
confidence: 68%
“…In isolated muscle strips from normal animal and human hearts, flosequinan appears to have a dose-dependent, positive inotropic effect, although this is not always observed in the therapeutic concentration range.2035-38 This is associated with a rise in intracellular Ca2+, but it does not appear to be mediated by a cyclic AMP-dependent mechanism because it is not enhanced in the presence of forskolin in most studies. 35,36,38 In muscle harvested from failing human hearts, conflicting findings have been observed. In one study, flosequinan did not increase contractility with or without forskolin stimulation.…”
Section: Discussionmentioning
confidence: 88%
“…It has also been shown, by analysis of heart rate variability, to reduce sympathetic activity and augment parasympathetic tone (Binkley et al, 1992). Some studies have demonstrated a positive inotropic action depending on the dosage (Perreault et al, 1991), preparation (Weishaar et al, 1991), and animal species tested (Greenberg et al, 1990). Even using the same invasive technique for assessing changes in contractility in patients has yielded conflicting results (Burstein et al, 1992;Starling, 1992a).…”
mentioning
confidence: 99%